Pastor-Principal Relationship in the Parish School - Weiss, Sharon (Catholic Education: A Journal of Inquiry and Practice, 2007)
The traditional parish plant”church, rectory, convent, and school”all conveniently located next to each other on a parcel of land, is a fast vanishing model. While some argue that the parish-sponsored elementary school is a vestige of immigrant Catholicism, this article calls for a strengthening of the relationship between the pastor and the principal. By using frames of reference from human resource management and organizational theory, this essay challenges pastors and principals to work through differences, find common ground and ways to collaborate, and resolve or set aside differences for the sake of the higher good.